Menakar tata kelola badan usaha milik desa di Indonesia - Harjanti Widiastuti; Wahyu Manuhara Putra; Evy Rahman Utami; Rudy Suryanto (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2019)
The purpose of this study is to identify the governance indicators and capture the governance practices of Village-Owned Enterprise (BUMDes). The contributions of the research are (1) constructing Village-Owned Enterprise’s governance indicators, which as far as the researcher knows, there has been no prior research, and (2) providing the preliminary description of Village-Owned Enterprise practices that have run. This research is a qualitative descriptive study. The research methods were literature study, focus group discussion, and survey. Focus group discussion was conducted with three Village-Owned Enterprises; BUMDes Amarta (Sleman), BUMDes Srimartani (Bantul), and BUMDes Dlingo Giritama (Bantul). Based on the results of the study, it showed that (1) most of the Village-Owned Enterprises that were the objects of the research were start-up and growing so that the basic governance were contained in the rules of association and internal bylaws (AD-ART) of Village-Owned Enterprise, but most of them have not compiled governance documents specially financial accountability documents, (2) the application level of Village-Owned Enterprise Governance in Indonesia was relatively low, the lowest element of applicability was in the sustainability and accountability aspects. This result seems to correlate with the period of Village-Owned Enterprises that is relatively new (three years in average). The indicators arranged are too ideal for start-up village-Owned Enterprises so that there are many indicators that have not been achieved. As a result, future research needs weighting indicators that can distinguish between start-up, growth and mature Village-Owned Enterprise. This research has implications on the requisite to provide the guidance for Village-owned Enterprise in terms of governance documents, such as Strategic Plans, Internal Control systems, and Financial Administration.